Protecting the Global Environment : Initiatives by Japanese Business - Cruz, Wilfredo; Fukui, Koichiro; Warford, Jeremy (Washington, DC: World Bank, 2013)
this volume is the result of a cooperative effort between the world Bank Institute and the Development Bank of Japan (DBJ) to encourage policy discussion of the links between global environmental concerns and national development policies and programs. The report is based on the premise that policymakers traditionally have not viewed global environmental problems, such as climate change, as collateral outcomes of their national sustainable development agenda. Therefore, the objective of this report is to present case studies that demonstrate how policy reform and investments can together produce national economic benefits while mitigating carbon emissions associated with climate change. These examples from Japan, which highlight the "software" aspects of change instead of the technology (for example, the important role of public-private sector cooperation, pricing incentives, and community participation) will be relevant for developing countries where the potential for these sources of change have not been sufficiently exploited.